Identifying the industrial sectors at risk of carbon leakage in China. (19th May 2017) - Wang, Xin; Teng, Fei; Zhou, Shaojie; Cai, Bofeng
Abstract : China is gradually establishing an Emissions Trading Scheme (ETS) to implement its plan to peak energy-related carbon emissions by 2030. A central debate on ETS design involves addressing the carbon leakage concern. In this study, a detailed quantitative assessment is conducted to identify the industrial sectors at risk of carbon leakage in China. The identification process is undertaken at the four-digit sector level according to the National Economic Industries Classification. Results show that the majority of emissions quotas must be allocated to several energy-intensive sectors. The criterion that focuses on maximum value at stake filters out 27 four-digit sectors, whereas the dual criterion of carbon and trade intensity highlights 17 four-digit sectors that are considered at actual risk of carbon leakage. Quantitative analysis results indicate that allocating 9% of emission quotas for free is sufficient to compensate these vulnerable sectors. The risk of exposure to carbon leakage can vary significantly due to the different levels of data disaggregation, as per the findings from the comparison of carbon intensity data obtained from four-digit sectors belonging to one two-digit sector in the Standard Industry Classification. Therefore, the importance of using high-quality disaggregated data is highlighted in this research. Official criteria for assessing the key indicators of industrial sectors must be designed to accurately evaluate the sectors at risk of carbon leakage. Policy relevance China is gradually establishing a nationwide Emissions Trading Scheme (ETS). The design of this scheme could significantly influence the economic profits and trade situation of industrial sectors. A central debate on the design of China's ETS involves how to address carbon leakage concerns; this question remains unanswered thus far. The evaluation of the extent to which the competitiveness of industrial sectors is affected by the ETS and the identification of sectors at risk of carbon leakage are certainly of practical significance to the design of an applicable range and an appropriate free quota allocation regime for China's ETS.